New dangerous practice on the horizon? Legal aspects of drone usage - Szikora, Veronika; Szilagyi, Gabor (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The reason why we have chosen this topic for the subject of this research is the new technologies emerging around us, particularly the unnamed aerial vehicles (UAV). In Hungary, similarly to some other countries, there is a gap in legislation concerning the use of UAV. The UAV technology raises many questions since these vehicles can be used for several purposes. It is necessary to analyze in depth the legal environment of UAV and to change our perspective as it is not enough to consider the legal context; technical and other aspects should be taken into consideration too. Most academic sources related to the usage of UAV focus on the military use of the technology. In our research, we put an emphasis on the various aspects of civil law; the reason for this approach is that we consider the legal restrictions concerning the ordinary vehicles used for everyday purposes and not for governmental ones. The main goal of our paper is to study how the usage of UAV can be legally controlled. This question is important as the number of these vehicles are gradually growing. This tendency raises several legal issues like privacy or tort. In our research, we have analyzed international laws and regulatory plans, national laws, and draft legislation. The „abnormally dangerous activities” that appear in the title of the paper is an indication that we consider the liability aspect of the problem an important issue. The other aim of our paper is to make a proposal to set up a work group that is going to work out the regulations in detail. Legislators and researchers could participate in the work group, among whom technical and legal professionals may merge their forces.